Monetary and Financial Statistics : Compilation Guide: Compilation Guide. (Manuals and Guides, 2008)
Monetary and Financial Statistics: Compilation Guide is a companion to the IMF's Monetary and Financial Statistics Manual (2000). It describes the economic sectorization, valuation, and other accounting rules used in compiling data on the financial assets and liabilities of the financial corporations sector and all economic sectors of an economy. This guide to best practices contributes to the IMF's ongoing initiatives to enhance data transparency and statistical standards among member countries, and thus to further the adoption of sound macroeconomic policies and the smooth functioning of global financial markets.